The institutional context of Old Testament scholarship in Africa - Holter, Knut (Old Testament essays, 1998)
In recent years several universities and theological seminaries throughout sub Saharan Africa have developed postgraduate programmes that encourage research related to the Old Testament. The article comments on two aspects of the institutional context of this research. First, with regard to official education and research policy, the first decades of independence challenged African universities and seminaries to contextualise their scholarly approaches and emphasise the question of relevance. And secondly, with regard to infrastructure and economic resources, a general under-funding of the universities and seminaries makes interaction with non-African scholarship difficult.